2006
DOI: 10.1149/1.2353607
|View full text |Cite
|
Sign up to set email alerts
|

Materials Issues for the Heterogeneous Integration of III-V Compounds

Abstract: GaAs, InP, GaSb, and InAs were investigated for layer transfer to other III-V substrates using hydrogen ion exfoliation and wafer bonding to develop III-V based wafer bonded templates for subsequent epitaxial growth of device structures. High-resolution X-ray diffraction was proven to be particularly helpful in this investigation enabling nondestructive testing of the initial implantation profile as well as the strain relief ͑associated with the diffusion of hydrogen and other point defects͒ after various anne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 30 publications
(38 reference statements)
2
44
0
Order By: Relevance
“…11,12 In addition, dependence between the lowest temperature required to trigger the nucleation process and the melting point of the implanted material has also been highlighted in previous work. 5 As the melting point of germanium ͑937°C͒ is close to the melting point of InP ͑1060°C͒, defect nucleation would be expected to occur at 150°C or below in hydrogen-implanted germanium. To study this effect, surface roughness measurements after long ͑22 h͒ anneal at 100, 130, or 150°C have been performed.…”
Section: A Low Temperature Hydrogen Diffusionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,12 In addition, dependence between the lowest temperature required to trigger the nucleation process and the melting point of the implanted material has also been highlighted in previous work. 5 As the melting point of germanium ͑937°C͒ is close to the melting point of InP ͑1060°C͒, defect nucleation would be expected to occur at 150°C or below in hydrogen-implanted germanium. To study this effect, surface roughness measurements after long ͑22 h͒ anneal at 100, 130, or 150°C have been performed.…”
Section: A Low Temperature Hydrogen Diffusionmentioning
confidence: 99%
“…2,3 The mechanisms which govern defect formation in H-implanted semiconductors and the creation of microcracks has already been extensively characterized in silicon, germanium, 4 and III-V compounds. 5 It is often addressed from a wafer bonding perspective and targets a range of applications varying from the fabrication of low defective substrates for complementary metal-oxide-semiconductor compatible applications ͓͑SOI and germanium-on-insulator substrates "GeOI" ͑Ref. 6͔͒ to advanced photonic devices like avalanche photodiodes and solar cells.…”
Section: Introductionmentioning
confidence: 99%
“…73 The implantation was performed with 150-keV H 2 + ions at a dose of 2 9 10 16 H 2 + cm -2 while cooling the substrates to a nominal value of À20°C, which is necessary to retain sufficient hydrogen for exfoliation, i.e., to avoid substantial dynamic annealing. After implantation of InAs substrates, they were bonded to SiN x -coated GaAs wafers.…”
Section: Other Semiconductorsmentioning
confidence: 99%
“…8-10 A few works have also reported on this phenomenon in some conventional compound semiconductors. [11][12][13] Techniques such as vibrational spectroscopies, [14][15][16][17][18][19] transmission electron microscopy, 10,20 Rutherford backscattering spectrometry in the channeling mode, [21][22][23] x-ray diffraction, 24 and positron annihilation spectroscopy 22,25 improved greatly our understanding of the microscopic mechanisms of the ion-cut process ͑particularly in Si͒. These studies have demonstrated the critical role of H-vacancy ͑H-V͒ complexes and damage-generated stress in the formation of nanoscopic platelets and voids immediately after implantation.…”
Section: Introductionmentioning
confidence: 99%